Investigation on the effect of lubrication and forming parameters to the green compact generated from iron powder through warm forming route - Rahman M.M.; Nor S.S.M.; Rahman H.Y. (2023)
In order to generate green compacts of iron ASC 100.29 powder at above ambient temperature and below its recrystallization temperature, a warm compaction rig is designed and fabricated which can be operated at various temperature and load. The aim of this paper is to present the outcomes of an investigation on the effect of lubrication and forming parameters, i.e., load and temperature to the green compacts generated through warm compaction route. The feedstock was prepared by mechanically mixing the main powder constituent, i.e., iron ASC 100.29 powder with different weight percent of zinc stearate at different mixing time. Compaction load was varied from 105. kN to 125. kN using simultaneous compaction mechanism. The microstructures of the green compacts were analyzed by Scanning Electron Microscopy (SEM), and the mechanical properties are measured through density measurement, hardness test and electrical conductivity test. The study found that increase in compaction load as well as forming temperature give improved microstructure and mechanical properties. It is also found that effects of lubrication to the mechanical properties of green compacts are strongly dependant on the lubricant content as well as mixing time of iron powder with the lubricant. 2010 Elsevier Ltd.